2004
DOI: 10.1210/en.2003-0478
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Programming: Prenatal Testosterone Excess Leads to Fetal Growth Retardation and Postnatal Catch-Up Growth in Sheep

Abstract: Alterations in the maternal endocrine, nutritional, and metabolic environment disrupt the developmental trajectory of the fetus, leading to adult diseases. Female offspring of rats, subhuman primates, and sheep treated prenatally with testosterone (T) develop reproductive/metabolic defects during adult life similar to those that occur after intrauterine growth retardation. In the present study we determined whether prenatal T treatment produces growth-retarded offspring. Cottonseed oil or T propionate (100 mg,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
192
10
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 231 publications
(220 citation statements)
references
References 72 publications
15
192
10
3
Order By: Relevance
“…For instance, in sheep, testosterone treatment of the mother during early to mid pregnancy reduced birth weight and height in the offspring of either gender (21). This supports the concept that fetal growth retardation, an early marker of adult diseases, can be initiated through prenatal excess exposure to sex steroids.…”
Section: Discussionsupporting
confidence: 57%
“…For instance, in sheep, testosterone treatment of the mother during early to mid pregnancy reduced birth weight and height in the offspring of either gender (21). This supports the concept that fetal growth retardation, an early marker of adult diseases, can be initiated through prenatal excess exposure to sex steroids.…”
Section: Discussionsupporting
confidence: 57%
“…This finding also indicates that in children with male co-twin versus a female co-twin intrauterine growth in general is increased. Indeed, in animals it has been reported that fetal growth can be programmed by prenatal exposure to sex steroids (42). On the other hand, as in our sample birth weight only explained 8% of the variance in total brain volume at 9 years of age, the use of birth weight as a proxy for prenatal testosterone exposure on brain volumes seems tenuous.…”
Section: Discussioncontrasting
confidence: 53%
“…In general, the ratio between the second (2D = index finger) and fourth (4D = ring finger) digits in men is lower than that observed in women (Lutchmaya et al, 2004;Manning et al, 1998). Anatomical evidence of prenatal androgen exposure has gained significance in recent times because there is growing evidence in animal models that adult traits and behaviors including, disease susceptibility may be programmed during fetal development (Abbott et al, 2006;Manikkam et al, 2004 Manning and Bundred, 2000;Robinson, 2006). Previous studies in humans have shown low digit ratios (2D:4D) to be associated with a variety of traits including, enhanced visual spatial ability (Burton et al, 2005;van Anders and Hampson, 2005), increased athleticism (Honekopp et al, 2006a), female homosexuality (Brown et al, 2002;Hall and Love, 2003;Kraemer et al, 2006;Williams et al, 2000), decreased susceptibility to coronary artery disease (Fink et al, 2003;Manning and Bundred, 2000), and greater fertility potential in men (Manning et al, 1998) but lower fertility potential in women (Cattrall et al, 2005).…”
mentioning
confidence: 99%